Understanding the Barriers to Accessing Symptom-Specific Cognitive Behavior Therapy (CBT) for Distressing Voices: Reflecting on and Extending the Lessons Learnt From the CBT for Psychosis Literature - Hazell, Cassie M.; Greenwood, Kathryn; Fielding-Smith, Sarah; Rammou, Aikaterini; Bogen-Johnston, Leanne; Berry, Clio; Jones, Anna-Marie; Hayward, Mark (Frontiers in Psychology, 2018)
The experience of hearing voices ('auditory hallucinations') can cause significant distress and disruption to quality of life for people with a psychosis diagnosis. Psychological therapy in the form of Cognitive Behavior Therapy for psychosis is recommended for the treatment of positive symptoms, including distressing voices, but is rarely available to patients in the UK. Cognitive Behavior Therapy for psychosis has recently evolved with the development of symptom-specific therapies that focus upon only one symptom of psychosis at a time. Preliminary findings from randomized controlled trials suggest that these symptom-specific therapies can be more effective for distressing voices than the use of broad CBT protocols, and have the potential to target voices trans-diagnostically. Whilst this literature is evolving, consideration must be given to the potential for a symptom-specific approach to overcome some of the barriers to delivery of evidence-based psychological therapies within clinical services. These barriers are discussed in relation to the UK mental health services, and we offer suggestions for future research to enhance our understanding of these barriers.